NFC Secured Offline Password Storage - Senthil Kumar; V. Mathivanan (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
In this paper is all about constructing a device called “One-WORD” that aims to solve this problem. One-word is an offline password keeper aimed at saving and encrypting the passwords in a more secure manner. The main device contains the encrypted passwords while a secure NFC smartcard and a personal pin-code allows the decryption. Even if an attacker is able to get hold the smartcard, or the device it is completely useless without the personal code.